A review of the effects of migration on the feminization of agrarian dryland economies - Baada, Jemima Nomunume; Najjar, Dina (Africa Centre for Gender, Social Research and Impact Assessment, 2020)
Intensifying outmigration in dryland areas affects women's roles in agriculture and related activities, with broader implications for productivity and gender equity. Using a systematic review of literature, we examine the effects of migration on the “feminization of agriculture” in dryland areas. The findings reveal that women are performing more farm labor in agrarian societies due to the increasing outmigration of men. In addition, female agricultural labor is becoming more visible because of growing research on the feminization of agricultural labor in dry areas. The findings also show that migration-related agricultural feminization in drylands is influenced by gendered, generational, socioeconomic, and sociocultural factors, as well as economic and social remittances – with ongoing negotiations of these processes happening at different levels. Despite the tensions and (re)negotiations that accompany these changes, particularly regarding return migration, social and economic policy interventions could leverage the increasing participation of women in dryland agriculture to improve women's livelihoods.